Rancang bangun meja dan kursi kerja untuk perbaikan postur kerja pada pekerja pengolah ikan berdasarkan pengukuran NBM dan RULA - Silvia Uslianti; Tri Wahyudi; Ratih Rahmahwati; Adelia Tamala (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
Slouching and squatting work postures in the fish cleaning process can cause skeletal muscle injury. Based on the results of previous research conducted by Adelia (2020), the results of the existing NBM show that workers have complaints in the muscles of the neck, arms, back, waist, buttocks, hands, wrists, thighs, knees, and feet. The result of total muscle complaints individual skeletal is 75, meaning that the existing work posture requires work improvement. Improvement of working posture can be done by designing work aids in the form of desks and chairs. The determination of the MSDs risk level category was carried out by identifying the skeletal muscle complaints felt by workers using a Nordic body map (NBM) questionnaire, a working posture assessment was carried out to determine the score level in work posture using the Rapid Upper Limb Assessment (RULA) method with the help of CATIA V5R20 software. Assistive devices in the form of desks and work chairs are designed based on complaints experienced by workers and use the anthropometric approach in determining the dimensions of work aids. Based on the results of the implementation of work aids, there was a change in the score for skeletal muscle complaints and work posture. The results showed that the average NBM value of individual muscle complaints was 56.75, this is included in the moderate risk level and the results of the RULA analysis on the repair work posture experienced a change in the final score, namely 4 (yellow).